Recurrent hypoplastic left heart syndrome associated with maternal diabetes mellitus. (18th April 2012) - Bird, A; Pinto, S; McIntyre, K
Abstract : We report a rare case of hypoplastic left heart syndrome (HLHS) occurring in two pregnancies of a mother with diabetes mellitus. The first pregnancy occurred three years following the diagnosis of type 2 diabetes. HbA1c during this pregnancy was 7.13% and insulin was commenced at 20 weeks gestation. Following delivery at 35 weeks the female baby showed signs of cyanotic congenital heart disease, was diagnosed with hypoplastic left heart syndrome and sadly died on day 12 of life. The mother remained on insulin. Two later pregnancies resulted in deliveries of live male babies, one with no evidence of congenital heart disease and the other with a large ventricular septal defect. The booking HbA1c level in these pregnancies was 6.1% and 11.2% respectively. In the final pregnancy, which was unplanned, the booking HbA1c level had been 9.2%. HLHS was again diagnosed, this time at 24 weeks gestation, and the pregnancy was subsequently terminated. A clinical geneticist had counselled the parents following their first pregnancy and a 1-2% recurrence risk of congenital heart disease was given. The sibling recurrence risk of HLHS has since been quoted as high as 8% (Hinton et al 2007). Research into the relationship between hypoplastic left heart syndrome and maternal diabetes has been conflicting (Loffredo 2001, Moore 2000, Ferencz 1997, Becerra 1990) but one study suggested that maternal insulin dependent diabetes is a significant risk factor for HLHS (Abu-Sulaimain 2004). This rare case may support the findings reported in this study. It also highlights the importance of preconception counselling with particular reference to achieving satisfactory glycaemic control prior to conception.